2022
DOI: 10.1186/s13071-022-05290-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple biochemical indices and metabolomics of Clonorchis sinensis provide a novel interpretation of biomarkers

Abstract: Background Clonorchiasis, an infectious disease caused by the liver fluke Clonorchis sinensis, may lead to the development of liver and gallbladder diseases, and even cholangiocarcinoma (CCA). However, the pathogenesis, host-pathogen interaction, and diagnostic markers for clonorchiasis remain unclear. Methods Eighteen rabbits were randomly divided into control group (n = 9) and C. sinensis-infected group (n = 9), and their plasma samples were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…In our earlier research, the alteration of amino acid metabolism was observed in rat spleen and serum infected with C. sinensis ( Zhang et al., 2020 ; Han et al., 2023 ). In addition, Qiu et al. (2022) found that the amino acid levels in the serum of rabbits were altered after C. sinensis infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our earlier research, the alteration of amino acid metabolism was observed in rat spleen and serum infected with C. sinensis ( Zhang et al., 2020 ; Han et al., 2023 ). In addition, Qiu et al. (2022) found that the amino acid levels in the serum of rabbits were altered after C. sinensis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a decrease in the quantity of extracellular glutamine makes cells more susceptible to apoptosis ( Chen and Cui, 2015 ). Studies have shown that the level of glutamine was significantly reduced in the serum of rabbits infected with C. sinensis ( Qiu et al., 2022 ). Therefore, we speculated that glutamate and glutamine may play important roles in distinguishing OB+C.s patients from OB patients.…”
Section: Discussionmentioning
confidence: 99%
“…C . sinensis metacercariae were obtained from naturally infected Pseudorasbora parva purchased from endemic areas in Changchun city, Jilin Province, China, and were orally administered to New Zealand white rabbits [ 27 ]. Adult worms were collected from the bile ducts of infected rabbits 5 weeks post-infection.…”
Section: Methodsmentioning
confidence: 99%
“…These results imply the crucial significance of transcriptome analysis in comprehending the survival strategies, respiratory processes, and metabolism of C . sinensis [ 11 ]. The differential gene expression and regulatory patterns across developmental stages and tissues provide valuable insights into the intricate biology of this parasite, thus providing information on potential targets for understanding its pathogenicity and for developing effective interventions.…”
Section: Introductionmentioning
confidence: 99%